Effects of misleading media coverage on public health crisis: a case of the 2019 novel coronavirus outbreak in China - Wen, Jun; Aston, Joshua; Liu, Xinyi; Ying, Tianyu (Anatolia : an international journal of tourism and hospitality research, 2020)
The coronavirus outbreak in Wuhan, China has sparked a global epidemic, which the World Health Organization declared a public health emergency of international concern on 31st January 2020 (Beijing time). This crisis has attracted intense media attention. Recently, some media outlets inappropriately labelled the coronavirus by race, using such headlines as "Chinese virus pandemonium" and even suggesting "China kids stay home." The biased and misleading coverage presented via Western media channels has incited anger throughout the Chinese community and has placed undue stress upon Chinese individuals living outside China. This post-published review takes a tourism-focused perspective to examine findings from a quantitative study (Rodriguez-Seijas, Stohl, Hasin, & Eaton, 2015) published in 2015 in JAMA Psychiatry. The current paper highlights the potential impacts of misleading and biased media coverage on Chinese individuals' mental health. Specifically, this work considers perceived racial discrimination stemming from coronavirus as a public health crisis and the effects of such discrimination on individuals of Chinese heritage. Similarly imperative are pertinent effects on country image and destination image with respect to tourism marketing and tourist behaviour during times of crisis. By considering racism in the context of the coronavirus outbreak, this paper identifies potential avenues for relevant research in tourism and hospitality.